Corporate Environmental Responsibility dalam Pencemaran Pulau-Pulau Kecil di Indonesia - Abdul Aziz Alsa; Devi Yulida (Fakultas Hukum, Universitas Warmadewa, 2025)
Corporate criminal liability for environmental pollution presents an intriguing subject of analysis, particularly in the context of Indonesia’s small islands, which possess limited ecological carrying capacity and are highly vulnerable to environmental degradation. This paper aims to examine the forms of corporate criminal liability in cases of environmental pollution on small islands and to assess the extent to which legislation can effectively reach and bind corporations as subjects of criminal law. This study employs a normative juridical method, using statutory and conceptual approaches. The findings reveal that although corporations cannot physically commit acts themselves, liability can be traced through the actions of directors or individuals holding authority within the corporate structure (the directing mind). Furthermore, considering Indonesia’s geographic characteristics, it is essential to strengthen a legal framework that is responsive to the socio-ecological conditions of small islands, in order to promote corporate accountability and ensure sustainable environmental protection.